FORMATION OF MITOCHONDRIA IN NEUROSPORA CRASSA : A Study Based on Mitochondrial Density Changes - Luck, David J. L. (The Rockefeller University Press, 1965)
The choline concentration used in the growth medium influences the density of mitochondria produced by the chol-1 mutant of Neurospora. Isopycnic centrifugation in sucrose gradients can be used to determine the density of mitochondria, and can resolve into two populations, mitochondria derived from a mixture of cells grown at low (1 µg/ml choline chloride) and high (10 µg/ml choline chloride) choline levels. In an experiment in which cells are shifted from low to high choline growth conditions, mitochondria obtained after varying time periods show a gradual decrease in density tending toward the level typical of high choline mitochondria. Over a 90-minute period of observation, during which time there is an increase of mitochondrial protein mass of ∼ 50 per cent over that initially present, the mitochondria change density as a single population. These results are consistent with the view that mitochondria grow by random accretion of new lecithin into existing mitochondrial structures, and also that the mitochondrial population increases by division.